`d/(dt) sin^-1t=1/sqrt(1-t^2)`

`y'=1/(sqrt(1-(2x+1)^2))*d/(dx) (2x+1)`

`y'=2/sqrt(1-(4x^2+1+4x))`

`y'=2/sqrt(1-4x^2-1-4x)`

`y'=2/sqrt(-4x^2-4x)`

`y'=2/sqrt(4(-x^2-x))`

`y'=2/(2(sqrt(-x(x+1))))`

`y'=1/sqrt(-x(x+1))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now